Electronic government and the information systems perspective : 7th International Conference, EGOVIS 2018, Regensburg, Germany, September 3-5, 2018, Proceedings /: 7th International Conference, EGOVIS 2018, Regensburg, Germany, September 3-5, 2018, Proceedings. (2018) - Unknown
No abstract available